PENGARUH MANAJEMEN PENGETAHUAN, MOTIVASI KERJA DAN KEPEMIMPINAN TERHADAP KINERJA PERSONIL ANGGOTA KEPOLISIAN BIDANG TEKNOLOGI INFORMASI DAN KOMUNIKASI POLDA SULTRA - Karunia Disatra; Ibnu Hajar; Salma Saleh (Pascasarjana Universitas Halu Oleo, 2022)
AbstractThis study aims to: 1) determine the simultaneous effect of knowledge management, work motivation and leadership on police performance, 2) determine the effect of knowledge management on police performance, 3) determine the effect of motivation on police performance, and 4) determine the effect of leadership on police performance.The object of this research is the TIK Polda Sultra. The population of the study was police officers who served in TIK Polda Sultra totaling 74 personnel. Because the number of population units is limited, the entire population unit at the same time becomes a prospective respondent for this study as many as 74 personnel. The research data was collected using a questionnaire, the research data was analyzed using SPSS ver 20 to determine the results of the regression analysis of the influence of the independent variable on the dependent variable.The results of the study: 1) The simultaneous and positive effect of knowledge management, work motivation, and leadership on the performance of members of the Southeast Sulawesi Regional Police's TIK, 2) Knowledge management has a positive and significant effect on the performance of the Southeast Sulawesi Regional Police's TIK Division, 3) Work motivation has a positive and significant effect on significantly to the performance of the members of the TIK Sector of the Southeast Sulawesi Regional Police, and 4) Leadership has a positive and significant effect on the performance of the members of the TIK Division of the Southeast Sulawesi Regional Police.